Parametric study on the hydrothermal synthesis of fluorescent p-doped carbon quantum dots from banana peels (Musa acuminata) and their photocatalytic performance towards hexavalent chromium reduction - Claus, Christian Marasigan; Detras, Monet Concepcion M; Capunitan, Jewel A; Carpio, Rowena B; del Barrio, Marilyn C (Center of Biomass & Renewable Energy (CBIORE), 2025)
Hexavalent chromium (Cr(VI)) represents a significant risk to both human health and the environment. Photocatalysis offers a promising method for reducing Cr(VI) to the less toxic Cr(III) state, which can be easily precipitated and removed. Carbon quantum dots (CQDs) have become prominent in photocatalysis owing to their facile synthesis, light-harvesting capacity, and electron transfer properties. In this study, banana peel (Musa acuminata) powder containing approximately 59.58 ± 7.43% (w/w) carbohydrates and 15.67 ± 0.15% (w/w) moisture, serves as a sustainable carbon source for synthesizing CQDs, through the hydrothermal method. Phosphoric acid was introduced as a dopant and catalyst, promoting the formation of fluorescent phosphorus-doped carbon quantum dots (P-CQDs). These P-CQDs were then used as photocatalysts for the visible light-induced reduction of Cr(VI). This research employed a 2k factorial experimental design to evaluate the effects of hydrothermal synthesis conditions such as phosphoric acid-to-banana peel powder mass ratio (1:1 to 2:1), reaction temperature (140°C to 180°C), and reaction time (4 to 8 hours) on the photoreduction of 50ppm Cr(VI) in synthetic wastewater. Photoreduction efficiencies ranged from 57.3% to 85.4% after 2 hours of visible light irradiation. Analysis of Variance (ANOVA) results at a 95% confidence interval demonstrated that all three factors significantly influenced the reduction efficiency. Furthermore, UV-Vis spectroscopy of P-CQDs at varying hydrothermal synthesis conditions revealed characteristic absorption bands at π–π* transitions of the C=C bonds in the core structure and n–π* transitions of C=O/P domains on the surface. Meanwhile, FTIR analysis of P-CQD samples has shown several peaks corresponding to hydroxyl, carbonyl, carboxyl and phosphorus-containing functional groups. The synthesized compound also exhibited strong photoluminescence with blue-green emission under 365 nm UV light. These findings are crucial for further research aimed at optimizing the synthesis of sustainable P-CQD photocatalysts.